Designing and building oncolytic viruses. (April 2017) - Maroun, Justin; Muñoz-Alía, Miguel; Ammayappan, Arun; Schulze, Autumn; Peng, Kah-Whye; Russell, Stephen
Oncolytic viruses (OVs) are engineered and/or evolved to propagate selectively in cancerous tissues. They have a dual mechanism of action; direct killing of infected cancer cells cross-primes anticancer immunity to boost the killing of uninfected cancer cells. The goal of the field is to develop OVs that are easily manufactured, efficiently delivered to disseminated sites of cancer growth, undergo rapid intratumoral spread, selectively kill tumor cells, cause no collateral damage and pose no risk of transmission in the population. Here we discuss the many virus engineering strategies that are being pursued to optimize delivery, intratumoral spread and safety of OVs derived from different virus families. With continued progress, OVs have the potential to transform the paradigm of cancer care.